MyD88-dependent signaling in non-parenchymal cells promotes liver carcinogenesis. (13th February 2019) - Mohs, Antje; Kuttkat, Nadine; Otto, Tobias; Youssef, Sameh A; De Bruin, Alain; Trautwein, Christian
Abstract: In Western countries, a rising incidence of obesity and type 2 diabetes correlates with an increase of non-alcoholic steatohepatitis (NASH)—a major risk factor for liver cirrhosis and hepatocellular carcinoma (HCC). NASH is associated with chronic liver injury, triggering hepatocyte death and enhanced translocation of intestinal bacteria, leading to persistent liver inflammation through activation of Toll-like receptors and their adapter protein myeloid differentiation factor 88 (MyD88). Therefore, we investigated the role of MyD88 during progression from NASH to HCC using a mouse model of chronic liver injury (hepatocyte-specific deletion of nuclear factor κB essential modulator, Nemo; Nemo Δhepa ). Nemo Δhepa ; Nemo Δhepa /MyD88 −/− and Nemo Δhepa /MyD88 Δhepa were generated and the impact on liver disease progression was investigated. Ubiquitous MyD88 ablation (Nemo Δhepa /MyD88 −/− ) aggravated the degree of liver damage, accompanied by an overall decrease in inflammation, whereas infiltrating macrophages and natural killer cells were elevated. At a later stage, MyD88 deficiency impaired HCC formation. In contrast, hepatocyte-specific MyD88 deletion (Nemo Δhepa /MyD88 Δhepa ) did not affect disease progression. These results suggest that signaling of Toll-like receptors through MyD88 in non-parenchymal liver cells is required for carcinogenesis during chronic liver injury. Hence, blocking MyD88 signaling may offer a therapeutic option to prevent HCC formation in patients with NASH. Abstract : Using a mouse model of chronic liver injury, we showed that ubiquitous (but not hepatocyte-specific) MyD88 ablation aggravated liver damage and impaired formation of hepatocellular carcinoma. These results implicate Toll-like receptor signaling through MyD88 as essential for liver carcinogenesis.